Magnetic Resonance Imaging of Cerebral Hemorrhagic Stroke - Dilbar, Khodjieva; Dildora, Khaydarova; Nodirjon, Khaydarov (International Journal of Psychosocial Rehabilitation, 2020)
A study was made of the diagnostic effectiveness of the method of magnetic resonance imaging (MRI) in the diagnosis of hemorrhagic stroke in the acute phase. An analysis of the data of 50 patients with hemorrhagic stroke at the age of 52-67 years was carried out. As a result of the study, it was shown that in the diagnosis of intracerebral hemorrhage, the T2* - weighted mode is most informative, which allows visualizing the presence of blood in the early stages of the development of a stroke. It is shown that the use of this regimen should be included in the protocol of MRI studies of patients with acute cerebrovascular accident. The conclusion is made about the wide possibilities of using MRI as a method of choice in the study of patients with suspected hemorrhagic stroke from the first hours from the onset of the disease.